'I am struggling to survive' - limited living conditions increase the burden of HIV: A qualitative study - Ingeborg Ulvund; Gezahegn Bekele Dadi; Anne Gutteberg (Taylor & Francis Group, 2023)
ABSTRACTThe human immunodeficiency virus (HIV) continues to have life-limiting health consequences for many individuals and remains a significant threat to global public health. This qualitative study explores the experiences of people living with HIV in Sidama, Ethiopia. Interviews with 19 adults recruited from an HIV outpatient clinic were conducted using a semi-structured interview guide. The analysis method used was systematic text condensation. The results reveal that an HIV diagnosis triggered strong emotions. Economic concerns, stigma, and discrimination also increased the burden of a diagnosis, which could lead to a loss of income or housing. Consequently, informants' ability to maintain a regular life and receive social and psychological support was reduced. Religious faith provided strength to informants, though they stated that some religious leaders do not support antiretroviral therapy. Understanding the everyday challenges of people living with HIV is crucial for health professionals and health programme developers working to promote health and enable people to follow their recommended course of treatment. Person-centred care is recommended. In particular, the poorest should receive attention. It is also crucial to reduce stigma and discriminatory attitudes towards people living with HIV and to motivate faith leaders to prevent HIV stigma and support antiretroviral therapy.